The use of research by public relations practitioners - Albert Anani-Bossman; Fortune Tella (Communicare)
The importance of research by public relations practitioners has been highlighted by leading scholars in most developed countries. However, studies show that the use of research by practitioners is more talked about than actually done. In Ghana, little is known about how practitioners use research. This paper therefore attempts to add to the limited literature by investigating whether public relations (PR) practice in Ghana is informed by research. Data was collected from 93 PR practitioners using a survey. The results suggest that although research is used by practitioners, the emphasis appears to be on media monitoring and content analysis. The implication is that research cannot be fully appreciated if it is based solely on the amount of publicity received. The value of PR in the eyes of management can only be enhanced if emphasis is placed on the impact and outcome of research. Practitioners must therefore use a more scientific approach in their research activities.